Gravity wave interaction with multiple submerged artificial reefs. (May 2021) - Vijay, KG; Neelamani, S; Nishad, CS; Sahoo, T
In the present study, gravity wave interaction with a series of submerged artificial permeable reefs is analysed within the framework of linearised water wave theory. For wave past porous walls of the artificial reefs, a quadratic pressure drop is assumed to account for the wave energy dissipation due to the changes in wave height. The physical problem is handled for a solution using a numerical model based on the iterative multi-domain boundary element method and the developed numerical model is validated with known results in the literature. The iterative model is compared with the numerical model based on linear pressure drop boundary condition (i.e., Darcy law). The study reveals that the wave transmission reduces with the increase in the number of reef units. It is demonstrated that the transmission coefficient can be reduced to less than 0.5 when the number of reef units is greater than or equal to three for a relative height greater than 0.7, reef porosities less than 20% and for 0.40 h<3.0. Bragg reflection is observed when the porosity is in the range of 0 to 10% and above which the recurrent nature of wave reflection gradually fades away due to dissipation effects. The number of peaks occurring in the shallow and intermediate water depths is equal to the number of reef units wherein the maxima occur at the first frequency. A relative increase in the base width improves the energy losses but the rate of increase in energy loss decreases. The scattering coefficient pattern is oscillatory when the relative spacing between the barriers is varied and their hydrodynamic performance is invariant for higher relative base width.